Against the Grain: The Tragedy of Zimbabwe in the Context of 4IR - Umali Saidi (Springer, Cham, 2022)
Most, if not all, African countries continue to seek solutions to socio-economic and political challenges facing their citizens. Previous ‘industrial’ revolutions resulted in more harm on the African continent than good or relief. Either African countries had to import various political, economic policies and strategies from the West and East as a result, in the hope of easing poverty and underdevelopment or had the same imposed on them by the powerful authors of Industrial Revolutions. Zimbabwe has, as it where, not been spared in this matrix. For the country, the Fourth Industrial Revolution (4IR) spells tragedy as the expected symbols of socio-economic and political transformation are far and beyond the horizon. Using key aspects of semiotics, symbols and representation, this chapter attempts to show how Zimbabwe, like most African countries, appears to be far from being ready to partake in the global revolution of economic essence and development largely because of being in a continued state of inertia, sluggish tendencies as well as having slow-moving ‘local revolutions’. The chapter further battles with two important questions that, were African countries ever ready for the previous three Industrial Revolutions, 1st, 2nd and 3rd? Is Africa ready for the current 4th Industrial Revolution? Will Africa ever be ready for the 5th, 6th, 7th or any forthcoming umpteenth revolutions which are more global than local? To engage these, and other related questions, the chapter hopes to onion-peel preparedness of Zimbabwe, and other African countries, to the 4IR. The chapter suggests ways on how Africa, and Zimbabwe in particular, can leapfrog as well as transform in order to benefit from these unavoidable global revolutions.